URGENT FACTORS RELATED TO THE INCIDENCE OF DEPRESSION IN ELDERLY IN KORONG TOBOH WORK AREA PUSKESMAS KAMPUNG DALAM - Aulia Asman, Debby Silvia Dewi (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
According to the survey results of the World Health Organization (WHO) 1990 every year there are 100 million cases of depression (Handajani, 2003). It is estimated that in the future (2020) Developing countries in disease patterns will change, ie unipolar major depression will replace respiratory diseases as the top down (Amir, 2005). The purpose of the study to determine the factors associated with mental disorders (depression) in the elderly dikorong Toboh Puskesmas village in 2014. Depression is a mood disorder. Mood is the atmosphere that is pervasive and persistent feelings experienced internally and that affects a person's behavior and their perceptions of the world (Sadock & Sadock, 2007) This study uses descriptive analytic study with cross sectional approach. The study was conducted in Korong Toboh Puskesmas In the village on 23 to 30 June 2014, all elderly study population aged over 60 years who are as much as 168 diKorong Toboh sampling technique is simple random sampling, 42 samples were obtained. SPSS data processing is done. The results showed the total sample of 42 respondents, 54.8%, has a female gender, 52.4% of respondents do not work, 64.3% supported no families and 61.9% had a mental disorder. There is a significant relationship between sex with the incidence of mental disorders (depression) in Korong Toboh Puskesmas In the village, There is a significant association between the incidence of work with mental disorders (depression) in Korong Toboh Puskesmas Village In and There is a significant association between kejandian family support with mental disorders (depression) in Korong Toboh Puskesmas Kampung in. It is expected that this research as an input and information for institutions and health workers in health centers in order to plan more effective programs, so as to provide information to the public about the factors associated with depression in the elderly and may prevent further occurrences.